Structural reconstruction of the graphene monovacancy. - Robertson, A; Montanari, B; He, K; Allen, C; Wu, Y; Harrison, N; Kirkland, A; Warner, J (2013)
Two distinct configurations of the monovacancy in graphene have been observed using aberration-corrected transmission electron microscopy (AC-TEM) at 80 kV. The predicted lower energy asymmetric monovacancy (MV), exhibiting a Jahn-Teller reconstruction (r-MV), has been observed, but in addition, we have imaged instances of a symmetric monovacancy (s-MV). We have used geometric phase analysis (GPA) to quantitatively determine the strain in the lattice surrounding these two defect configurations and show that the Jahn-Teller reconstruction generates significant extra strain compared to the symmetric MV case. Density functional theory calculations demonstrate that our experimental images of the two different monovacancies show good agreement with both the low energy r-MV and the metastable structures.